1999
DOI: 10.1109/42.781014
|View full text |Cite
|
Sign up to set email alerts
|

Off-resonance correction of MR images

Abstract: In magnetic resonance imaging (MRI), the spatial inhomogeneity of the static magnetic field can cause degraded images if the reconstruction is based on inverse Fourier transformation. This paper presents and discusses a range of fast reconstruction algorithms that attempt to avoid such degradation by taking the field inhomogeneity into account. Some of these algorithms are new, others are modified versions of known algorithms. Speed and accuracy of all these algorithms are demonstrated using spiral MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…12, we used the formulation in Eq. [5] as part of an inverse problem approach to field-inhomogeneity-corrected image reconstruction (i.e., estimate the image f given the field map, ). We showed that in regions with large field inhomogeneity, the iterative reconstruction method results in more accurate images than the standard conjugate phase approach.…”
Section: Nonlinear Least-squares Joint Estimationmentioning
confidence: 99%
“…12, we used the formulation in Eq. [5] as part of an inverse problem approach to field-inhomogeneity-corrected image reconstruction (i.e., estimate the image f given the field map, ). We showed that in regions with large field inhomogeneity, the iterative reconstruction method results in more accurate images than the standard conjugate phase approach.…”
Section: Nonlinear Least-squares Joint Estimationmentioning
confidence: 99%
“…3). The problem becomes increasingly severe at higher fields; therefore, methods for distortion corrections have found increasing interest (27)(28)(29)(30)(31)(32)(33)35). All of these approaches are based on measurements of local field variations by additional field map measurements integrated into the examination.…”
Section: Signal Behavior In Bold Fmrimentioning
confidence: 99%
“…[10], if the regularization parameter values are fixed, then b ϭ (A WA ϩ R) Ϫ1 A Wd , where R ϭ I␤ ϩ ⌳. This analytical solution involves a matrix inversion, which is a computationally intensive O(N t 3 ) operation.…”
Section: Theorymentioning
confidence: 99%
“…Afterwards, the sample values are compensated for density variation in the trajectory. Some researchers have designed pulses by adopting the conjugate-phase (CP) approach from image reconstruction (9,10), which accounts for off-resonance effects and thus can correct for it to some extent (11,12).…”
mentioning
confidence: 99%